Florida’s Forest Stewardship Program: An Opportunity to Manage Your Land for Now and the Future - Mary L. Duryea; Deborah McGrath; Chris Demers; Anthony Grossman (EDIS)
The Forest Stewardship Program encourages landowners to manage their lands for multiple natural resources, increases public awareness of the importance of Florida’s forestlands, and improves cooperation among natural resource agencies and organizations to meet Florida’s forest resource conservation and management needs. This three page fact sheet written by Mary Duryea, Deborah McGrath, Chris Demers, and Anthony Grossman and published by the School of Forest Resources and Conservation explains the program and its benefits and describes how to become a forest steward.